Knowledge and Practice of Bio Medical Waste Management in a Mortuary and Casualty of Tertiary Care Hospital (Indian Journal of Forensic Medicine & Toxicology, 2020)
Bio Medical Waste management has been receiving highest priority in hospitals after the act was introducedby the Ministry of Environment and Forest, titled Bio Medical Waste Management and Handling Rules 1998.About 0.33 million tons of waste is generate per annum in India. Hospital acquired infections are on the risedue to improper waste management practice. A cross sectional, longitudinal study on Bio Medical wastemanagement practice in a mortuary and casualty was conducted at a tertiary care teaching hospital from 1stJuly 2018 to 31st December 2018. The study focused on knowledge and practice of waste management inthe casualty and mortuary. Interestingly, the practice of Bio Medical waste management was excellent incasualty and mortuary. Awareness of the hazards of improper waste management was poor among sanitaryworkers whereas doctors, nurses and other paramedical staff were well aware of the hazards.